Analisis Komunikasi Pemasaran Berbasis Online di Masa Pandemi pada Perusahaan Penerbit Buku RGP - Gita Garliani; Yandi Hermawandi; Haryadi Mujianto (JIKA (Jurnal Ilmu Komunikasi Andalan), 2021)
Along with the sophistication of technology and the behavior of people who prefer to move at home using the internet during a pandemic, product marketing can now be integrated with online-based marketing. Online-based marketing strategies are important, especially when the COVID-19 pandemic hits Indonesia, where people prefer to do activities at home using the internet. The background of this research is the existence of community activities in cyberspace (internet) during the pandemic which makes companies need to optimize their online-based marketing communications. One of the business fields that are required to follow the online-based marketing style during this pandemic is the book publishing company PT Raja Grafindo Persada (RGP). This study will analyze online-based marketing communications during the pandemic at the book publishing company PT RGP. The research method used is a qualitative method that will describe the marketing of book products during a pandemic which can be seen from PT RGP's online-based marketing communications. The data collection method in this study will use the method of observation, documentation, and literature study to produce data validity. The activity that was chosen purposively was the online marketing communication activity of the publisher PT RGP during the pandemic. The results showed that the publisher of PT. RGP, especially during this pandemic, carried out online-based marketing communications optimally. They perform 5 stages of optimally integrated marketing communications.